Degree of Meaningfulness of an Event's Ending Can Modulate Mixed Emotional Experiences Among Japanese Undergraduates. Issue 4 (August 2022) - Shirai, Mariko; Kimura, Toshiaki
While people may experience mixed emotions when confronting a meaningful ending; it is unclear how much an ending's meaningfulness contributes to evoking these mixed emotions. This study examined, among Japanese undergraduate students, whether different degrees of meaningfulness of an ending affected emotional experiences, and how time passage changed emotional intensity. Sixty-one Japanese students (37 females, 24 males; M age = 20.75, SD = 0.80) reported their emotional experiences and the degree of meaningfulness they assigned to the ending of the Heisei era at two time points-before and after the ending. As expected, participants who placed high meaningfulness to the ending of the Heisei era experienced a high level of mixed emotions, indicating that the degree of meaningfulness given to an ending can modulate emotional experiences. Furthermore, the specific emotions experienced (i.e., sadness or happiness) differed depending on the assessment time point, such that the meaningfulness of the ending played a key role in producing mixed emotional experiences in this sample.